2022
DOI: 10.1530/eor-21-0113
|View full text |Cite
|
Sign up to set email alerts
|

Double fixation for complex distal femoral fractures

Abstract: For complex distal femoral fractures, a single lateral locking compression plate or retrograde intramedullary nail may not achieve a stable environment for fracture healing. Various types of double fixation constructs have been featured in the current literature. Double-plate construct and nail-and-plate construct are two common double fixation constructs for distal femoral fractures. Double fixation constructs have been featured in studies on comminuted distal femoral fractures, distal femoral fracture with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Popular options of double fixation of a comminuted distal femur fracture include a dual plating construct or a nail-and-plate construct [ 13 , 14 ]. Stoffel reviewed multiple studies in 2022 [ 15 ]. Although there was no statistical analysis, he concluded that both constructs gave high union rates and satisfactory functional outcomes; choosing which constructs to use relied on balancing the pros and cons with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Popular options of double fixation of a comminuted distal femur fracture include a dual plating construct or a nail-and-plate construct [ 13 , 14 ]. Stoffel reviewed multiple studies in 2022 [ 15 ]. Although there was no statistical analysis, he concluded that both constructs gave high union rates and satisfactory functional outcomes; choosing which constructs to use relied on balancing the pros and cons with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Stoffel et al have suggested placing oblique screws at the ends of the plates to enhance fixation strength. [ 36 ] We prefer using as many locking screws as possible in the distal fragment and bending the proximal end screw.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Ruchholtz et al , Ehlinger et al and Wood et al concluded that minimally invasive techniques should be the preferred treatment for PPFFs fixation ( 28 , 29 , 30 ). Kanakaris et al and Wood et al discussed that despite the potential advantage of smaller less invasive procedures with less blood loss and improved fracture biology, this should not be at the expense of a malreduced fracture ( 24 , 30 ).There is clear data that adequate fracture reduction and femoral axis alignment, avoiding varus deformity, are crucial to prevent delayed union or mechanical complications ( 31 , 32 , 33 ). All delegates agreed that open reduction should be considered, when necessary, to avoid malreduction.…”
Section: Discussionmentioning
confidence: 99%